Morphometric Assessment of the Cerebellum of the Pre-implanted albino Rats Embryos after Maternal Exposure to AgNPs - Israa Hassan Ali (Journal of Global Pharma Technology, 2016)
Cerebellum (cb) is the most important and sensitive part of the central nervous system (CNS) after cerebrum. The exposure to any infection during embryogenesis produces abnormalities in the cerebellum function and morphology that effect on behavioral of offspring later. In the present study we used 30 mature female pregnant albino rats divided in to three groups, each group contain 10 females: G1 was considered the control group received D.W only, while G2 group treated orally with (2mg/kg /day) suspension of silver nanoparticles (AgNPs) and G3 group treated orally with (20mg/kg/day) AgNPs. The embryos retrieved in different embryonic days from ED12 to ED21. In this study morphometric analysis was measured in the developing albino rats cerebellum after maternal exposure to two concentrations of AgNPs from pre- implantation period until delivery . we measured the morphometric parameters  (area, perimeter, anterior-posterior diameter APD and transverse diameter TD) of the selected embryonic days; ED12,ED15,ED18, and ED21 and retrieved the embryos from these days. The morphometric results in the control group(G1) showed that increased significantly (P≤ 0.05) in the area of the developing cerebellum from ED12 until reach the optimal level in the end of gestation at ED21 (14.0815mm2 to 18.969 mm2 respectively), perimeter (9.804 mm2 to 16.267 mm2) and TD (52.6308µm to 431.6 µm),while the APD value was increased significantly (P≤ 0.05) at ED12 and ED15 only (367.0041 µm, 454.011 µm )respectively but the orientation growth of the cerebellum decreased significantly (P≤ 0.05) at the later stage of the development at ED18 and ED21(364.48 µm, 225µm) respectively. In the present research both  concentrations of the AgNPs (2mg and 20 mg/kg/ B.Wt) showed changes in the dimensions of the developing cerebellum cortex according to the studied morphometric parameters; in the 2 mg/kg/ B.Wt, the area of the developing cerebellum cortex was increased significantly (P≤0.05) from ED12 (47.437mm 2) and reached to maximum growth at ED18 (130.220 mm2), while it is growth inhibited at ED21( 68.909 mm2) compared to control group, the values of the developing cerebellum cortex perimeter increased significantly (P≤0.05) from ED12 until ED15 (0.964 mm 2, 2.548 mm 2)  respectively compared to control group; TD values of the developing cerebellum cortex increased significantly (P≤0.05) from ED12 until ED15 also (259.341 µm,436.203 µm) respectively compared to control group. While the APD of the developing cerebellum cortex was decreased significantly (P≤0.05) during late development of the cortex at ED18 and ED21(330.415 µm, 131.5 µm) respectively as in the control group. In G3 group which treated with 20mg/kg/ B.Wt concentration of AgNPs, the similar results of area were showed as in the lower concentration, area of the developing cortex increased significantly (P≤0.05) from ED12(80.11mm 2) and reached to maximum growth at ED18(140.56 mm2) and lower after that. the values of the developing cerebellum cortex perimeter increased significantly (P≤0.05) from ED12 until ED15 (0.256 mm2, 0.543 mm2)  respectively compared to control group; while in the APD and TD values the effect of the higher concentration of the AgNPs was more effect on these dimensions; APD values decreased significantly (P≤0.05) at ED15 (360.48 µm ) and not reach to the complete growth, also in TD values decreased at ED15 (400.5744 µm) and do not reach to maximum growth at end embryonic development compared to the embryonic development timing in the control group.Keywords:  AgNPs, Pre-implantation, Cerebellum, ED, Albino rats.